Building world order how the Christian faith fosters global peace, prosperity, and justice - Amstutz, Mark R. 1944- (Lanham Boulder New York London Rowman & Littlefield, 2025)
"The international community is beset with problems, and the order and prosperity of global society can only be realized through the collaborative work of nation-states. Building World Order argues that Christian values can contribute to the common good by guiding public service in government, nongovernmental organizations, and individual action"--
Includes bibliographical references and index
Keywords: Christianity and international relations; Conflict Management -- Religious aspects -- Christianity; Peace-building -- Religious aspects -- Christianity; Justice -- Religious aspects -- Christianity; Globalization -- Religious aspects -- Christianity